2017
DOI: 10.1186/s13046-017-0520-6
|View full text |Cite
|
Sign up to set email alerts
|

iASPP induces EMT and cisplatin resistance in human cervical cancer through miR-20a-FBXL5/BTG3 signaling

Abstract: BackgroundEpithelial–mesenchymal transition (EMT) and dysregulated microRNAs (miRNAs) have important roles in driving chemoresistance. We previously reported that iASPP is a key EMT inducer and could increase cisplatin resistance in cervical cancer (CC) cells. Herein, we investigate the downstream mechanisms through which iASPP contributes to EMT and cisplatin resistance in CC.MethodsBy using a lentiviral system, we investigated the effects of iASPP knockdown on CC cell growth and chemosensitivity of CC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Notably, Yao et al, showed post-surgical patients with high expression of FBXL5 had shorter overall survival than patients with low FBXL5 expression [24]. Based on our data suggesting AM404's effect in CSC-like activity (Figure 2), and recent studies indicating FBXL5 regulating CRC metastasis [23,25,26], we then wanted to elucidate whether AM404 exerted its noted effects via FBXL5 in CRC cells [24,26,27]. We have therefore generated CRISPR-Cas9 mediated FBXL5-knockout in DLD-1 cell line ( Figure 6B and Figure S6).…”
Section: Fbxl5 Attenuates Am404-induced Anticancer Activitysupporting
confidence: 74%
See 1 more Smart Citation
“…Notably, Yao et al, showed post-surgical patients with high expression of FBXL5 had shorter overall survival than patients with low FBXL5 expression [24]. Based on our data suggesting AM404's effect in CSC-like activity (Figure 2), and recent studies indicating FBXL5 regulating CRC metastasis [23,25,26], we then wanted to elucidate whether AM404 exerted its noted effects via FBXL5 in CRC cells [24,26,27]. We have therefore generated CRISPR-Cas9 mediated FBXL5-knockout in DLD-1 cell line ( Figure 6B and Figure S6).…”
Section: Fbxl5 Attenuates Am404-induced Anticancer Activitysupporting
confidence: 74%
“…Currently, there is no established data available for AM404 in colorectal cancer. Our data suggest that ubiquitin-ligase FBXL5 [24][25][26][27], might be a key target through which AM404 utilizes its pharmacological effects on CRC cells.…”
Section: Introductionmentioning
confidence: 85%
“…Here, we reported that miR-20a is downregulated in osteosarcoma and indicated that miR-20a is a tumorsupressor in osteosarcoma cell growth. miR-20a downregulation was reported in cutaneous squamous cell carcinoma, future science group www.futuremedicine.com hepatocellular carcinoma and pancreatic cancer cells [18][19][20], whereas its upregulation was shown in uveal melanoma, colorectal cancer and cervical cancer [21][22][23]. These controversial data indicate that the function of miR-20a is possibly tumor specific and highly dependent on its downstream target in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…miR-20a can also inhibit proliferation and induce the apoptosis of hepatocellular carcinoma cells in vitro by targeting the anti-apoptotic member myeloid cell leukemia sequence 1 protein of the Bcl-2 family (48). The expression of miR-20a in glioma, cervical cancer, gastric cancer, lung carcinoma, neuroblastoma and prostate cancer, and its corresponding target genes and their functions, are presented in Table II (46,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). However, the upregulation or downregulation of miR-20a expression in a number of tumors is not consistent in numerous previous studies due to the differences in cell lines and limited sample sizes (47,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79).…”
Section: Microrna-20a Overviewmentioning
confidence: 99%
“…However, the chemotherapy resistance of CRC cells is challenge in the treatment of patients with CRC (119). Studies have indicated that miR-20a induces cisplatin resistance in numerous cancers, potentially including in CRC (55,57,111,112). The miR-20a inhibitor can sensitize cisplatin-induced CRC cytotoxicity via the reactive oxygen species (ROS) pathway.…”
Section: Mir-20a May Be Used As a Monitoring Indicator During Chemothmentioning
confidence: 99%